(untitled) (Atlas Journal of Biology, 2017)
Herbaria are libraries of dried mounted plants used for plant identification, research vouchers and teaching. Herbarium specimens are subject to damage from insects, fungi and bacteria, and must be protected by treatments that kill damaging organisms. Naphthalene, the most common chemical currently used in herbaria, is a class C carcinogen and potential allergen. The aim was to develop an affordable alternative to treatment with persistent hazardous toxins for maintaining dried herbarium specimens. The new method uses ambient temperature nitrogen gas and widely available, valved, nylon, oxygen barrier bags. Nitrogen gas treatment has been shown to be less expensive than freezer storage and safer than treatment with naphthalene and other toxins. The lower hazard of nitrogen treatment compared to naphthalene offers a practical option for K-12 and institutions of higher education to initiate, reinstate or strengthen herbarium collections for teaching and/or research. This is the first report of the use of inexpensive valved oxygen barrier bags for herbarium pest control.